Ar+ implantation-induced tailoring of RF-sputtered ZnO films: structural, morphological, and optical properties - Manu Bura; Divya Gupta; Arun Kumar; Sanjeev Aggarwal (Beilstein Journal of Nanotechnology, 2025)
Radio frequency-sputtered zinc oxide films are implanted with 30 keV Ar+ ions at various fluences ranging from 1 × 1015 to 2 × 1016 ions·cm−2. Raman spectra reveal the presence of the E2 (low), E2 (high), and A1 (LO) Raman modes in pristine and implanted ZnO films. A gradual fall and rise in peak intensity of, respectively, the E2 (high) and A1 (LO) Raman modes is observed with increases in ion fluence. However, the E2 (low) mode broadens and merges completely with disorder-induced broad band at higher fluences. Moreover, the deconvolution of the A1 (LO) Raman peak affirms the presence of defect-related Raman modes in the implanted samples. A gradual reduction in crystallinity of the implanted ZnO films with increasing ion fluence is observed in grazing incidence angle X-ray diffraction patterns. Atomic force microscopy images show grain size reduction and a fall in the surface roughness value of films after implantation. The implantation-induced structural modifications are further correlated with the variation in diffuse reflectance, Urbach energy, and optical bandgap. The low reflectance values of implanted films assure their suitability as transparent windows and anti-reflective coating in various optoelectronic devices.